PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS DAN LIKUIDITAS TERHADAP KEBIJAKAN DIVIDEN DAN NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Firlana Akbar; Irham Fahmi (Departemen Manajemen, 2020)
This study aims to determine the effect of company size, profitability and liquidity on dividend policy and company value in manufacturing companies listed on the Indonesia Stock Exchange (IDX). This study uses a purposive sampling technique with several criteria to obtain 21 samples from companies listed on the Indonesia Stock Exchange during the 2013-2017 period. The analytical method used in this study is a multiple linear regression analysis. The results showed that company size had a positive and not significant effect on dividend policy, profitability had a positive and significant effect on dividend policy, liquidity had a positive and not significant effect on dividend policy, company size had a positive and not significant effect on firm value, profitability had a positive and significant effect on firm value, Liquidity has a negative and significant effect on firm value, and dividend policy has a positive and not significant effect on firm value.